Experimental analysis of behavior and damage of sandwich composite materials in three-point bending. Part 1. Static tests and stiffness degradation at failure studies - Bezazi, A.; El Mahi, A.; Berthelot, J.-M.; Bezzazi, B. (Проблемы прочности, 2007)
The analysis of stiffness and the identification
of rupture mechanisms during and after static
tests of sandwich panels and their components
have been investigated. The sandwich panels,
having cross-ply laminates skins made of glass
fibre and epoxy resin were manufactured by
vacuum moulding and subjected to three-point
bending tests. Two PVC cores of similar type
but with differing densities were investigated.
The effect of core density and its thickness on
the behavior and the damage was highlighted.
In terms of stiffness and load at failure, the
sandwich structure has better mechanical
characteristics compared to its components. Експериментально досліджено зміну жорсткості та проаналізовано механізми
руйнування при статичних випробуваннях багатошарових композитних
пластин і їх компонентів. Багатошарові композитні пластини з перехресними
шарами зі скловолокна та епоксидної смоли, що виготовлені
методом вакуумної відливки, піддавали навантаженню триточковим згином. Досліджували два варіанти пластин з однотипними наповнювачами з полі-
вінілопласта різної щільності. Розглянуто вплив щільності і товщини внутрішнього
шару наповнювача на поведінку та пошкодження композита. Показано,
що композит із наповнювачем великої щільності має більш високі
характеристики статичної міцності і стійкості порівняно з композитом із
наповнювачем меншої щільності. Экспериментально исследовано изменение жесткости и проанализированы механизмы разрушения
при статических испытаниях многослойных композитных пластин и их компонентов.
Многослойные композитные пластины с перекрестными слоями из стекловолокна и
эпоксидной смолы, изготовленные методом вакуумной отливки, подвергали нагружению
трехточечным изгибом. Исследовали два варианта пластин с однотипными наполнителями
из пеновинилопласта различной плотности. Рассмотрено влияние плотности и толщины
внутреннего слоя наполнителя на поведение и повреждение композита. Показано, что
композит с наполнителем большей плотности обладает более высокими характеристиками
статической прочности и устойчивости по сравнению с композитом, имеющим наполнитель
меньшей плотности.